SharePoint in Office 365 - Christie, Jason; Safari eBooks ([Place of publication not identified] : CompuWorks, 2016)
"This course is an introduction to Office 365 sites. Upon completion of this course, users will have a basic understanding of sites, navigation, libraries, searching, newsfeeds, views, permissions, and organization."--Resource description page.
Title from resource description page (Safari, viewed September 13, 2016).
Presenter, Jason Christie.
Keywords: Microsoft SharePoint (Electronic resource); Microsoft Office; Intranets (Computer networks); Electronic books